Unraveling the Long Tail Phenomenon. An Investigation into Netflix Series Consumption Patterns - Naldi, Maurizio; Fantozzi, Paolo; Dalla Torre, Paola (The Matter of Intellectual Property: Studying the Economic, Political and Cultural Nodes of the Contemporary Media Industries. 15th Media Mutations International Conference, 2025)
This study investigates content consumption patterns on Netflix through the lens of the long tail phenomenon, the Pareto principle, and concentration indices. Using Netflix’s public Engagement Report data from January to June 2023, encompassing 18,214 TV series, we analyze viewer behavior to explore the distribution of viewing times and their implications for content strategy and platform economics. The findings reveal a highly skewed distribution where the top 20% of series account for 85.6% of total viewing time, confirming an extreme Pareto distribution. However, a very low Hirschman-Herfindahl Index (HHI = 0.0007855) suggests a fragmented consumption landscape. We further discuss how licensed content, original productions, and branding influence viewer engagement and the broader implications for Netflix’s bundle-based business model.